2015
DOI: 10.1007/s11207-015-0750-8
|View full text |Cite
|
Sign up to set email alerts
|

Do All Candle-Flame-Shaped Flares Have the Same Temperature Distribution?

Abstract: We performed a differential emission measure (DEM) analysis of candle-flameshaped flares observed with the Atmospheric Imaging Assembly onboard the Solar Dynamic Observatory. The DEM profile of flaring plasmas generally exhibits a double peak distribution in temperature, with a cold component around log T ≈ 6.2 and a hot component around log T ≈ 7.0. Attributing the cold component mainly to the coronal background, we propose a mean temperature weighted by the hot DEM component as a better representation of fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 34 publications
0
35
1
Order By: Relevance
“…Using Yohkoh/SXT data, Tsuneta (1996) found that a cusp-shaped flare had hot plasma on the outer edges of the cusp, with a channel of cooler, denser plasma down the middle. Gou et al (2015) surveyed many cuspshaped flares using AIA and found that most of them adhered to this pattern. Guidoni et al (2015) study a flare using AIA data and find a similar temperature structure, but without the cooler channel.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Using Yohkoh/SXT data, Tsuneta (1996) found that a cusp-shaped flare had hot plasma on the outer edges of the cusp, with a channel of cooler, denser plasma down the middle. Gou et al (2015) surveyed many cuspshaped flares using AIA and found that most of them adhered to this pattern. Guidoni et al (2015) study a flare using AIA data and find a similar temperature structure, but without the cooler channel.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies have suggested that integrating only the high temperature component in Equation 1 provides a better characterization of the temperature of the supra-arcade plasma (e.g. Gou et al 2015). However, we elect to integrate over the entire DEM because we are also interested in the temperature of the voids associated with the SADs.…”
Section: Thermal Properties Of Supra-arcade Plasmamentioning
confidence: 99%
See 2 more Smart Citations
“…The comparisons of the reconstructions and the observations show that the reconstructions for 94Å and 335Å fit the observations poorly. Previous studies also show that the reconstruction errors at 94Å and 335Å are relatively larger than at other passbands (Hanneman & Reeves 2014;Gou et al 2015). The DEM errors using the spectra (triangle) predicted by CHIANTI 8 and the Feldman abundance are smaller than those using the spectra (diamond) predicted by CHIANTI 7 and the same coronal abundance for the 94Å band, apparently because of the improved atomic rates.…”
Section: Comparison Of the Observations And The Reconstructions From Demmentioning
confidence: 83%